2016
DOI: 10.1002/1873-3468.12125
|View full text |Cite
|
Sign up to set email alerts
|

NuclearDrosophilaCerS Schlank regulates lipid homeostasis via the homeodomain, independent of the lag1p motif

Abstract: Edited by Laszlo NagyDrosophila Ceramide Synthase (CerS) Schlank regulates both ceramide synthesis and fat metabolism. Schlank contains a catalytic lag1p motif and, like many CerS in other species, a homeodomain of unknown function. Here, we show that the Drosophila CerS Schlank is imported into the nucleus and requires two nuclear localization signals (NLSs) within its homeodomain and functional Importin-b import machinery. Expression of Schlank variants containing the homeodomain without functional lag1p mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 44 publications
2
22
0
Order By: Relevance
“…The single Drosophila Cers ortholog, Schlank, also has a homeodomain, in addition to the Lag motif. Interestingly, schlank mutants could be rescued by expression of variant proteins lacking a functional Lag motif, as long as they contained the homeodomain and a nuclear localization signal ( Voelzmann et al, 2016 ). While the mechanism for Cers2b action during zebrafish embryogenesis remains unclear, our results suggest the critical role played by this ER/nuclear membrane-localized enzyme is in autoregulation of sphingolipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The single Drosophila Cers ortholog, Schlank, also has a homeodomain, in addition to the Lag motif. Interestingly, schlank mutants could be rescued by expression of variant proteins lacking a functional Lag motif, as long as they contained the homeodomain and a nuclear localization signal ( Voelzmann et al, 2016 ). While the mechanism for Cers2b action during zebrafish embryogenesis remains unclear, our results suggest the critical role played by this ER/nuclear membrane-localized enzyme is in autoregulation of sphingolipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, upon addition of 5% coconut oil to the diet, Schlank indeed regained its localization to the nuclear membrane ( Fig 5D, 5F, 5H and 5I ) in the Pex2 , Pex3 , and Pex19 mutants we analyzed and would thus be enabled to repress lip3 , explaining the observed decrease in lip3 expression, reduced free fatty acid levels, ameliorated mitochondrial morphology, and rescue to adulthood. To further prove this hypothesis, we overexpressed a shortened version of Schlank (Schlank aa1–138 ) [ 38 , 27 ], which is constitutively nuclear (supplemental file S3 Fig ), in the Pex19 mutant background. We found that forcing Schlank into the nucleus in this manner rescues the lethality of Pex19 mutants ( Fig 5J ).…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, Drosophila has gained traction as an efficient model to study lipid metabolism in general (for a review, see Kühnlein, 2012) and sphingolipids in particular (Acharya and Acharya, 2005; Kraut, 2011; Bauer et al, 2009; Voelzmann et al, 2016). However, there is still a lack of knowledge concerning the degradation of membranes and in particular sphingolipids in Drosophila .…”
Section: Discussionmentioning
confidence: 99%